Near‐Unity Polarization of Valley‐Dependent Second‐Harmonic Generation in Stacked TMDC Layers and Heterostructures at Room Temperature. Issue 29 (12th June 2020) - Zhang, Danliang; Zeng, Zhouxiaosong; Tong, Qingjun; Jiang, Ying; Chen, Shula; Zheng, Biyuan; Qu, Junyu; Li, Fang; Zheng, Weihao; Jiang, Feng; Zhao, Hepeng; Huang, Lanyu; et al.
Abstract: With unique valley‐dependent optical and optoelectronic properties, 2D transition metal dichalcogenides (2D TMDCs) are promising materials for valleytronics. Second‐harmonic generation (SHG) in 2D TMDCs monolayers has shown valley‐dependent optical selection rules. However, SHG in monolayer TMDCs is generally weak; it is important to obtain materials with both strong SHG signals and a large degree of polarization. In the work, a variety of inversion‐symmetry‐breaking (3R‐like phase) TMDCs (WSe2, WS2, MoS2 ) atomic layers, spiral structures, and heterostructures are prepared, and their SHG polarization is studied. Through circular‐polarization‐resolved SHG experiments, it is demonstrated that the SHG intensity is enhanced in thicker samples by breaking inversion symmetry while maintaining the degree of polarization close to unity at room temperature. By studying TMDCs with different twist angles and the spiral structures, it is found that there is no significant effect of multilayer interlayer interaction on valley‐dependent SHG. The realization of strong SHG with high degree of polarization may pave the way toward a new platform for nonlinear optical valleytronics devices based on 2D semiconductors. Abstract : Enhanced SHG intensity with near‐unity polarization from inversion‐symmetry‐broken 2D TMDC atomic layers, spiral structures, and heterostructures are realized at room temperature. It is found that there is no significant effect of multilayer interlayer interaction on SHG polarization.